2021
DOI: 10.3390/f12111488
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Charcoal on the Properties, Enzyme Activities and Microbial Diversity of Temperate Pine Forest Soils

Abstract: Relict charcoal hearths (RCHs) increases soil fertility in forest ecosystems. However, the effects of RCHs on the activity and abundance of soil microorganisms remain unknown. In this paper, we analysed the impact of relict charcoal production on the soil enzymatic activity and composition of soil bacterial and fungal communities in Scots pine forests of the Manowo Forest District in northern Poland. Moreover, we determined the effect of relict charcoal production on the soil properties. Our research was condu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
8
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 76 publications
3
8
0
1
Order By: Relevance
“…In addition, there was a significantly higher activity of arylsulfatase in the OMC horizon. These findings concur with those of Lasota et al [26], who also reported higher levels in the OMC horizon. This same follow-up assessment (Figure 8) also confirmed increased activity in five extracellular enzymes that are involved in the transformation of C, N, P, and S (Tables 3 and 5), an effect also noted by Lasota et al [57].…”
Section: Charcoal-rich Layer Biochemistrysupporting
confidence: 93%
See 1 more Smart Citation
“…In addition, there was a significantly higher activity of arylsulfatase in the OMC horizon. These findings concur with those of Lasota et al [26], who also reported higher levels in the OMC horizon. This same follow-up assessment (Figure 8) also confirmed increased activity in five extracellular enzymes that are involved in the transformation of C, N, P, and S (Tables 3 and 5), an effect also noted by Lasota et al [57].…”
Section: Charcoal-rich Layer Biochemistrysupporting
confidence: 93%
“…Unlike the chemical and physical properties of the kiln soil environment, the biochemical nature of kiln platform soils is still largely unexplored. Nevertheless, there is some evidence that both the activity and diversity of soil microbiota can increase over time following the abandonment of such kilns, particularly in acidic edatopes [26].…”
Section: Introductionmentioning
confidence: 99%
“…Forests constitute one of the largest and most important ecosystems on Earth, covering over 40 million km 2 and accounting for 30% of the total land area in the world [ 1 , 24 ]. The ecology of forest soils is an important area of research due to the role of forests as carbon sinks.…”
Section: Discussionmentioning
confidence: 99%
“…Organic matter and its decomposition products cause soil acidification, leaching of elements, supply of nutrients, and modification of sorption properties [ 22 , 23 ]. In turn, the effect of soil on vegetation is most notable in the characteristic species composition of the natural forest complex related to the properties of a given part of the soil [ 3 , 24 ]. In the almost common view of foresters, soil is the least changed, most stable indicator complex and could be used to diagnose a habitat in any case, even where there is no tree stand and typically developed forest floor vegetation [ 24 , 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…It also plays a vital role in regional and local climate conditions globally. To date, a large number of studies have been carried out on the impacts of soil organic carbon (SOC) and the nutrient characteristics of soil [ 11 , 12 ], whereas fewer studies have been conducted on the relationship between the microbial properties of soil and enzymatic activities [ 13 , 14 , 15 ]. The activity of soil enzymes greatly influences nutrient cycling, and it plays an important role in sustainable development in agriculture [ 16 ].…”
Section: Introductionmentioning
confidence: 99%